2022
DOI: 10.3389/fnut.2022.1037186
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products in diabetic retinopathy and phytochemical therapy

Abstract: Advanced glycation end products (AGEs) are generated by the nonenzymatic glycation of proteins or lipids. Diabetic retinopathy (DR) is one common complication in patients with diabetes. The accumulation of AGEs in retinal cells is strongly associated with the development of DR. AGEs can induce the breakdown of redox balance and then cause oxidative stress in retinal cells, exerting cytopathic effects in the progression of DR. The interaction between AGEs and the receptor for AGE (RAGE) is involved in multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…The relevance of a number of disorders in the genesis of AMD is reported. In fact, retinal specific autophagy alterations [94,95], blue light-induced autophagy failure leading to an excess of oxidized substrates [52,54,59,[96][97][98][99][100][101], and systemic metabolic disorders suppressing retinal autophagy, such as diabetes [102,103] and familial dyslipidemia [104,105], are detrimental in AMD. It is established that a sitespecific autophagy suppression in the retina leads to AMD.…”
Section: Dysfunctional Autophagy In the Inner Choroid/outer Retina Is...mentioning
confidence: 99%
“…The relevance of a number of disorders in the genesis of AMD is reported. In fact, retinal specific autophagy alterations [94,95], blue light-induced autophagy failure leading to an excess of oxidized substrates [52,54,59,[96][97][98][99][100][101], and systemic metabolic disorders suppressing retinal autophagy, such as diabetes [102,103] and familial dyslipidemia [104,105], are detrimental in AMD. It is established that a sitespecific autophagy suppression in the retina leads to AMD.…”
Section: Dysfunctional Autophagy In the Inner Choroid/outer Retina Is...mentioning
confidence: 99%
“…It is interesting to note that aldosterone may be involved in the expression of VEGF and contribute to the development and progression of DR. Additionally, previous studies have highlighted the significant involvement of advanced glycation end products (AGEs), receptors for AGE, and nuclear factor erythroid 2-related factor 2 (NRF2) in the pathogenesis and progression of DR (30,31). Kang et al (32) demonstrated that AGE significantly increases VEGF mRNA expression in cells, indicating a positive correlation between AGE and VEGF levels. Moreover, recent research on diabetic nephropathy revealed that blocking receptors for AGE reduces aldosterone's negative impact on NRF2 signal mediators in renal cells, suggesting that aldosterone may block the binding of AGE and RAGE to reduce VEGF production and affect NRF2, leading to corresponding harm to the retina (33).…”
Section: Effect Of Aldosterone-mediated Angiogenesis On Diabetic Reti...mentioning
confidence: 99%
“…Kang et al. ( 32 ) demonstrated that AGE significantly increases VEGF mRNA expression in cells, indicating a positive correlation between AGE and VEGF levels. Moreover, recent research on diabetic nephropathy revealed that blocking receptors for AGE reduces aldosterone’s negative impact on NRF2 signal mediators in renal cells, suggesting that aldosterone may block the binding of AGE and RAGE to reduce VEGF production and affect NRF2, leading to corresponding harm to the retina ( 33 ).…”
Section: Effect Of Aldosterone-mediated Angiogenesis On Diabetic Reti...mentioning
confidence: 99%
“…The accumulation of circulating AGEs in retinal cells strongly correlates with DR ( Kang et al, 2022 ). Diet is a major source of AGEs, and long-term AGE intake leads to their cumulation in body fluids, contributing to the pathogenesis of diabetic retina.…”
Section: Posttranslational Modifications In Diabetic Retinopathymentioning
confidence: 99%